Analysis of the Influence of Gear Related Factor on the Thermo- elastic Coupling Deformation based on the Response Surface Method - Wang Chunhua; Jia Xiaoming; Li Zhen; Fan Changda (Jixie chuandong)
For analyzing the influence of related factors on gear thermo- elastic coupling deformation,based on the response surface method and the sample- point test method,the function relation between the gear thermo- elastic coupling deformation and related factor is constructed,gained by analyzing,the influence factors of tooth width,rotational speed,torque,boundary temperature on gear maximum thermo- elastic coupling deformation are- 0. 207,0. 273,0. 321 and 0. 199. According to the size and the positive and negative of these influence factors,the boundary temperature,tooth width,speed and torque have larger and larger influence on maximum deformation. The maximum deformation increased with the rotational speed,torque and boundary temperature,and decreased with the tooth width.